Heritage Tourism Ecosystem For Intangible Living Heritage Of Traditional Performing Arts At George Town World Heritage Site - Tee, Anthony Mooi Kwong (2021)
The prime objective of this research is to establishment of a framework of an ecosystem comprising of component, functions and criteria that sustain the practices of traditional performing arts with stakeholders‘ role and collaboration management in sustaining the intangible living heritage of traditional performing arts; an art cluster of creative economy and attraction of heritage tourism through qualitative research employing purposive sampling and framework technique